Educación progresista y su impacto en el desarrollo de habilidades socioemocionales en los estudiantes del 8vo EGB de la UE Guillermo Baquerizo Jiménez del Cantón Babahoyo - Goyes Samaniego, Carla Danixa (2025)
The research analyzed the impact of progressive education on the development of socio-emotional skills. The background includes relevant studies such as that of Figueroa and Zambrano (2023), which demonstrated a 45% increase in emotional self-regulation and assertive communication skills, and Paredes et al. (2022), which found a significant positive correlation (r=0.76) between progressive methods and the development of socio-emotional competencies. The problem identified is the need to strengthen socio-emotional skills at the Guillermo Baquerizo Jiménez Educational Unit, where DECE records indicate significant challenges: 40% of cases with difficulties in conflict resolution, 35% with social adaptation problems, and 30% with difficulties in emotional expression. The main objective is to determine the impact of progressive education on the development of socio-emotional skills in 8th grade EGB students during the period 2024-2025. The research uses a mixed approach, combining quantitative and qualitative methods. The population comprises 39 students and 3 teachers from eighth grade, working with the entire population because it is manageable. Collection techniques include student surveys and semi-structured interviews with teachers. The anticipated results suggest a significant improvement in the development of socio-emotional skills through the implementation of progressive strategies, including better emotional self-regulation, greater teamwork capacity, and better communication skills. In conclusion, it is expected that progressive education will prove to be an effective approach for the comprehensive development of socio-emotional competencies in basic education students. This research will contribute to the educational field by providing empirical evidence on the effectiveness of progressive approaches in the Ecuadorian educational context.